Project Feasibility Study of PLN Electricity Installation in Palm Oil Mill - Dila, Novita Ratna; Harwati, Harwati (Innovative: Journal Of Social Science Research, 2024)
X is a Palm Oil Mill in North Kalimantan with 60 tons/hour operating capacity. PT. X processes Fresh Fruit Bunch from its own plantation into Crude Palm Oil and Palm Kernel. In its operational activities, PT. X requires electricity to operate production machines, lighting, and other operational needs. Currently, the electricity requirement for its operations uses 2000 kVA Steam Turbine with 400 kVA and 1029 kVA Generators. However, using generators requires high costs, especially diesel costs. Therefore, PT. X is considering other alternatives to reduce electricity costs by installing electricity from PT Perusahaan Listrik Negara (PLN). The PLN electricity installation project at PT. X requires expensive investment costs, for the cost of the cost of building PLN substations, customer substations, and installing electrical devices and digging cables. The project feasibility study is required based on non-financial and financial aspects. Based on non-financial aspects (legal, environment, technical, and management), using PLN electricity is more profitable than using generator. Project feasibility study of the financial aspect calculated in 10 years period. Based on the financial aspect, the Internal Rate of Return (IRR) is 72.2%, Net Present Value (NPV) is Rp. 17,285,538,368.50, Payback Period (PP) is 2 years, and Return on Investment (ROI) is 133.05%. So, this PLN electricity installation project is feasible and profitable for the Palm Oil Mill.